Recombinant vesicular stomatitis viruses from DNA. - Lawson, N D (1995)
We assembled a DNA clone containing the 11,161-nt sequence of the prototype rhabdovirus, vesicular stomatitis virus (VSV), such that it could be transcribed by the bacteriophage T7 RNA polymerase to yield a full-length positive-strand RNA complementary to the VSV genome. Expression of this RNA in cells also expressing the VSV nucleocapsid protein and the two VSV polymerase subunits resulted in production of VSV with the growth characteristics of wild-type VSV. Recovery of virus from DNA was verified by (i) the presence of two genetic tags generating restriction sites in DNA derived from the genome, (ii) direct sequencing of the genomic RNA of the recovered virus, and (iii) production of a VSV recombinant in which the glycoprotein was derived from a second serotype. The ability to generate VSV from DNA opens numerous possibilities for the genetic analysis of VSV replication. In addition, because VSV can be grown to very high titers and in large quantities with relative ease, it may be possible to genetically engineer recombinant VSVs displaying foreign antigens. Such modified viruses could be useful as vaccines conferring protection against other viruses.